(Muslim) Woman in Need of Empowerment: US FOREIGN POLICY DISCOURSES IN THE ARAB SPRING. Issue 1 (2nd January 2016) - Saleh, Layla
Abstract: Why, in the current geo-political and strategic context seemingly in stark contrast to the "War on Terror, " does the emphasis on women in US foreign policy persist? Why the repeated references to the vulnerability of women who "need" US help to become "empowered" in the countries of the Arab Spring? An examination of US policymakers' discourses indicates a neo-orientalist biopolitical construction of the (Muslim) female population as one in perpetual need of "empowerment, " presumably by American or western benefactors. Public statements by US foreign policy officials, discussions of government programs and Congressional testimony add to the repertoire of a western-constructed archaeology of neo-orientalist knowledge of Islam. Further, these gendered discursive "imperial encounters" create open-ended possibilities for US interventionist policies in the region for years to come. The Arab (Muslim) woman may have participated in sparking and sustaining revolutions and even bringing down dictators, but she must still be trained and taught – by Americans or westerners. The sometimes didactic, often foreboding "concern" for her empowerment is more nuanced, but no less significant, than the professed commitment to "saving" her as justification for military operations in the heyday of the War on Terror.